Penerapan prosedur pengajuan dan penyelesaian pengurangan pensiunan Pajak Bumi dan Bangunan terhadap Penerimaan Asli Daerah pada BPPD Wilayah UPT Tengah Kota Bandung - Luci Septianti; Dyah Purnamasari (Politeknik Ganesha Medan, 2022)
In applying the procedure for submitting and completing the reduction of the Land and Building tax pension on the original local revenue at the BPPD in the Central UPT area of ??Bandung. The formulation of the problems studied in this study are 1. How is the application of the Land and Building Tax pension application at the BPPD in the Central UPT area of ??Bandung City. 2. How is the settlement effort in granting a reduction in Land and Building Tax pensions at the BPPD in the Central UPT area of ??Bandung. The purpose of this study is to find out how to submit a reduction and what requirements are needed in an application for a reduction in PBB and what are the obstacles and how to resolve the reduction in PBB against local revenue at the BPPD in the Central UPT area of ??Bandung City. The method used in this study is qualitative, namely research procedures that use descriptive written or spoken words that are observed. This research is located at the BPPD Office in the UPT Central Bandung area. By conducting interviews, observing and studying related documents at the BPPD in the Central Bandung UPT area, it can be concluded that the functions involved, the forms used and the application of the submission procedures are still not in accordance with SPIP such as officers receiving incomplete application files. Therefore, socialization is very necessary to provide information to taxpayers regarding the procedures and what requirements are needed in the submission and settlement of the PBB pension reduction.